2021
DOI: 10.1021/acsnano.1c00842
|View full text |Cite
|
Sign up to set email alerts
|

Pushing Optical Switch into Deep Mid-Infrared Region: Band Theory, Characterization, and Performance of Topological Semimetal Antimonene

Abstract: The existing pulsed laser technologies and devices are mainly in the infrared spectral region below 3 μm so far. However, longer-wavelength pulsed lasers operating in the deep mid-infrared region (3–20 μm) are desirable for atmosphere spectroscopy, remote sensing, laser lidar, and free-space optical communications. Currently, the lack of reliable optical switches is the main limitation for developing pulsed lasers in the deep mid-infrared region. Here, we demonstrate that topological semimetal antimonene posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Using synthesized multilayer antimonene as saturable absorbers, passively Q-switched pulsed lasers at 2 and 3.5 µm wavelengths were realized and the results indicate that multilayer antimonene is a promising optical switch for extending pulsed lasers into the deep mid-IR region. [126] Huang et al have fabricated and studied antimony structural allotropes copper oxide of Cu(111) through atomically-resolved scanning tunneling microscopy (STM). The author has reported the Figure 12.…”
Section: Electronic and Optoelectronic Applicationsmentioning
confidence: 99%
“…Using synthesized multilayer antimonene as saturable absorbers, passively Q-switched pulsed lasers at 2 and 3.5 µm wavelengths were realized and the results indicate that multilayer antimonene is a promising optical switch for extending pulsed lasers into the deep mid-IR region. [126] Huang et al have fabricated and studied antimony structural allotropes copper oxide of Cu(111) through atomically-resolved scanning tunneling microscopy (STM). The author has reported the Figure 12.…”
Section: Electronic and Optoelectronic Applicationsmentioning
confidence: 99%
“…Xue et al [ 19 ] assembled antimonene nanosheets on the surface of a gold chip using layer-by-layer technology and found that the sensitivity of antimonene to the SPR sensor varies with different thicknesses, which is defined as the ratio of the change in resonance angle to the change in the refractive index of the analyte, which is at least 2.3 times higher than existing miRNA sensors, even many orders of magnitude higher. It has a high refractive index in ultraviolet [ 20 ] and nonlinear characteristic behaviors [ 21 , 22 ] in optical properties and has applications in lasers [ 23 , 24 ] and laser protection [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of graphene can result in additional fabrication complexity. Other techniques to create optical switches include controlling the position of liquid droplets [18], or the use of liquid crystals [19], Dirac semimetals [20], and topological semimetals based on antimonene [21]. A notable advantage of VO2 over the other approaches is that the extreme difference between its metallic and insulating phase enable very high modulation depths [15] that can occur in rapid time scales in case the phase transition is induced by probe lasers.…”
Section: Introductionmentioning
confidence: 99%